2016
DOI: 10.1080/09168451.2016.1204219
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin 3,7-O-dimethyl ether from Siegesbeckia pubescens suppress the production of inflammatory mediators in lipopolysaccharide-induced macrophages and colon epithelial cells

Abstract: Siegesbeckia pubescens (Compositae) is an annual herb indigenous to Korean mountainous regions. Recent reports have been issued on some compounds derived from S. pubescens for its anti-inflammatory activity or mode of action. The quercetin 3,7-O-dimethyl ether (QDE) isolated from the herbs of S. pubescens suppressed the lipopolysaccharide (LPS)-induced nitric oxide and inducible nitric oxide synthase (iNOS) protein production in mouse macrophages. QDE downregulated pro-inflammatory cytokines such as interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Expression of Pro-inflammatory Cytokines 14) The level of IL-8 was determined using enzyme-linked immunosorbent assay (ELISA) kits (BD OptEIA , CA, U.S.A.) in HT-29 human colonic epithelial cells. The levels of IL-1β and IL-6 were detected by mouse ELISA kits (Cusabio, Wuhan, China) in RAW264.7 mouse macrophage cells.…”
Section: )mentioning
confidence: 99%
“…Expression of Pro-inflammatory Cytokines 14) The level of IL-8 was determined using enzyme-linked immunosorbent assay (ELISA) kits (BD OptEIA , CA, U.S.A.) in HT-29 human colonic epithelial cells. The levels of IL-1β and IL-6 were detected by mouse ELISA kits (Cusabio, Wuhan, China) in RAW264.7 mouse macrophage cells.…”
Section: )mentioning
confidence: 99%
“…Various pro-inflammatory signaling molecules were shown to play a role in colitis pathogenesis. For example, enhanced expression/activity profile of the MAPK family members (p38 MAPK, JNK, and ERK1/2) [ 27 , 46 ], PI3K [ 47 , 48 ], and the pro-inflammatory COX-2 [ 49 52 ] was observed in the colonic biopsies of IBD patients as well as in different animal models of colitis [ 25 ]. In addition, using chemical inhibitors of these pro-inflammatory molecules ameliorated colitis severity.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that they possess anti-inflammatory properties. Luteolin, genistein, quercetin and quercetagetin inhibited LPS-induced expression of inflammatory mediators such as TNFα and NO by suppressing NF-κB activation [ 22 – 24 ]. Furthermore, these flavonoids exerted inhibitory effects on IkB degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no effect of quercetin on COX-2 expression. We also reported that luteolin inhibited nuclear localization and transcriptional activation of NF-κB [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation